2023
DOI: 10.1001/jamahealthforum.2022.4936
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Utilization Rates Among Commercially Insured Adults in the US During the First Year of the COVID-19 Pandemic

Abstract: ImportanceThe COVID-19 pandemic has been associated with an elevated prevalence of mental health conditions and disrupted mental health care throughout the US.ObjectiveTo examine mental health service use among US adults from January through December 2020.Design, Setting, and ParticipantsThis cohort study used county-level service utilization data from a national US database of commercial medical claims from adults (age >18 years) from January 5 to December 21, 2020. All analyses were conducted in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…However, this limitation is unlikely to substantially affect the results because the intervention and comparison groups were similarly affected by the pandemic, and patterns of MH and SUD treatment had largely stabilized by 2021. 29 Fourth, we found a small but statistically significant differential trend in the volume of dispensed MH/SUD prescriptions in the 12 months prior to the policy change, although this is unlikely to alter our conclusion that there was no overall association of NCS with the volume of dispensed MH/SUD prescriptions in the first 6 months after the law's implementation. Fifth, we only observed dispensed prescriptions and have no information on prescriptions that were written but not dispensed or whether patients took dispensed medications.…”
Section: Limitationscontrasting
confidence: 56%
See 1 more Smart Citation
“…However, this limitation is unlikely to substantially affect the results because the intervention and comparison groups were similarly affected by the pandemic, and patterns of MH and SUD treatment had largely stabilized by 2021. 29 Fourth, we found a small but statistically significant differential trend in the volume of dispensed MH/SUD prescriptions in the 12 months prior to the policy change, although this is unlikely to alter our conclusion that there was no overall association of NCS with the volume of dispensed MH/SUD prescriptions in the first 6 months after the law's implementation. Fifth, we only observed dispensed prescriptions and have no information on prescriptions that were written but not dispensed or whether patients took dispensed medications.…”
Section: Limitationscontrasting
confidence: 56%
“…Third, the 2021 to 2022 study period happened during the COVID-19 pandemic, likely affecting trends in MH/SUD treatment. However, this limitation is unlikely to substantially affect the results because the intervention and comparison groups were similarly affected by the pandemic, and patterns of MH and SUD treatment had largely stabilized by 2021 . Fourth, we found a small but statistically significant differential trend in the volume of dispensed MH/SUD prescriptions in the 12 months prior to the policy change, although this is unlikely to alter our conclusion that there was no overall association of NCS with the volume of dispensed MH/SUD prescriptions in the first 6 months after the law’s implementation.…”
Section: Discussionmentioning
confidence: 74%
“…The percent of the population with any medical visit declined by at least one-third in April 2020 for all specialties examined except psychiatry, which increased 1.6% ( P < .001) (Table 2). Psychiatrists, who before the pandemic were far more likely to offer telehealth services than other specialties, were in the best position to rapidly switch from in-person to telehealth visits (McBain et al, 2023; Weinfield et al, 2023; Zhu et al, 2022). The percent with any visit to an ophthalmologist declined by 71% from April 2019 to April 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 7% to 20% of women during pregnancy suffer clinically relevant symptoms of depression, making it one of the most critical health concerns for mothers [ 29 31 ]. Recent studies found that many women with mental health conditions during the COVID-19 pandemic missed or avoided doctor visits, losing the opportunity to effectively manage their conditions [ 32 , 33 ]. Consistent with previous reports, the current study found that women with depression compared to those without it tended to have greater difficulties receiving prenatal care for reasons such as facility closures, COVID-19-related reasons, and family care.…”
Section: Discussionmentioning
confidence: 99%